English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Rewrite the equation -5x – 6y = -12 as a function of x.

2007-05-25 08:09:59 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

5x + 6y = 12
5x = 12 - 6y
x = (1/5).(12 - 6y)
x = 12/5 - (6/5).y

2007-05-25 22:01:04 · answer #1 · answered by Como 7 · 0 0

-6y = -12 + 5x

6y = 12 - 5x

y = 2 - (5/6)x

2007-05-25 15:16:03 · answer #2 · answered by fred 5 · 1 0

-5x - 6y = -12

-5x = -12 + 6y

x = 12/5 - 6y/5

Remember to watch your signs.

2007-05-25 15:13:39 · answer #3 · answered by Lady Geologist 7 · 0 2

-5x-6y= -12
-5x= -12+6y
5x=12-6y
x= (12-6y)/5

2007-05-25 15:15:39 · answer #4 · answered by cappuccino_lava 6 · 0 2

The one where y = stuff is correct. "A function of x" means that the variable not x (like y) is by itself.

2007-05-25 15:17:57 · answer #5 · answered by KWO James 1 · 0 0

fedest.com, questions and answers